The mechanism of berberine alleviating metabolic disorder based on gut microbiome - Han Wang; Han Wang; Haiyu Zhang; Zezheng Gao; Qiqi Zhang; Chengjuan Gu (Frontiers in Cellular and Infection Microbiology, 2022)
With socioeconomic advances and improved living standards, metabolic syndrome has increasingly come into the attention. In recent decades, a growing number of studies have shown that the gut microbiome and its metabolites are closely related to the occurrence and development of many metabolic diseases, and play an important role that cannot be ignored, for instance, obesity, type 2 diabetes (T2DM), non-alcoholic fatty liver disease (NAFLD), cardiovascular disease and others. The correlation between gut microbiota and metabolic disorder has been widely recognized. Metabolic disorder could cause imbalance in gut microbiota, and disturbance of gut microbiota could aggravate metabolic disorder as well. Berberine (BBR), as a natural ingredient, plays an important role in the treatment of metabolic disorder. Studies have shown that BBR can alleviate the pathological conditions of metabolic disorders, and the mechanism is related to the regulation of gut microbiota: gut microbiota could regulate the absorption and utilization of berberine in the body; meanwhile, the structure and function of gut microbiota also changed after intervention by berberine. Therefore, we summarize relevant mechanism research, including the expressions of nitroreductases-producing bacteria to promote the absorption and utilization of berberine, strengthening intestinal barrier function, ameliorating inflammation regulating bile acid signal pathway and axis of bacteria-gut-brain. The aim of our study is to clarify the therapeutic characteristics of berberine further and provide the theoretical basis for the regulation of metabolic disorder from the perspective of gut microbiota.